Psycho-emotional status of residents from radiation-polluted territories of Ukraine, born before and after the accident on the CHNPP (Environment & Health, 2022)
Objectiv. Determining the attitude of residents from radiation-contaminated areas (RCA) born before and after the Chernobyl accident to the state of their health, their social and environmental factors.Materials and methods. Analysis of the psycho-emotional state of RCA residents under the age of 18 on the date of the Chernobyl accident and those born in the post-accident period from 1987 to 1997 was conducted during their medical examination according to the program of Clinical and Epidemiological Register (CER) for adults (over 18 years). The study results of the state of psychosomatic health of RCA residents (1534 people born before the accident and 1010 people after the accident) for the post-accident period (1993-2016) were obtained during the survey.Results: The majority of RCA residents born before the Chernobyl accident said (75.75%) that they already had a disease before the Chernobyl accident. In the period after the accident, 81.01% of respondents in this group reported deterioration and a severe deterioration in health. Of this group, 40.86% of respondents attributed the loss of their health to the impact of negative factors, including: 26.78% - social and professional and only 14.08% - with the Chernobyl accident. A significant number (39.43%) had answers "other factors" or "I do not know". Living on RCA as a factor in the development of anxiety, emotional tension, deteriorating health of the residents, their relatives, children, grandchildren now and in the future, indicated only 24, 57% of respondents and 21.99% of residents did not think that this factor affects the deterioration of their health. Among the measures that can prevent the deterioration of psychosomatic health, 44.45% of residents born before the accident considered effective - medical measures (regular inpatient and spa treatment, diet, physical therapy).The majority of residents born after the accident (62.64%) rated their current health status as "excellent" and "good". Some respondents (33.59%) indicated satisfactory health and 3.79% - poor health (against 60.10% and 26.86%, respectively, among those born before the accident). More than a half of those born after the accident said that living on RCA "does not affect" their health.Among the social measures that can improve health and prevent the development of diseases, half of respondents (50.0%) noted long vacations and physical activities, sports. Almost half of the residents in both groups did not know or pointed to other medical and social measures to restore and maintain their health.Conclusions:1. Analysis of the socio-psychological survey results of RCA residents showed that the psycho-emotional state of residents born before the Chernobyl accident was much worse compared to residents born after the accident, as evidenced by malaise, anxiety, nervous tension.2. The lack of awareness of RCA residents about the harmful effects of ionizing radiation, even in small doses, on their health leads to inadequate threat assessment and disregard for the rules of conduct in this area and is a lack of educational work among victims.
Keywords: residents of radiation-polluted territories; status health; psycho-emotional status